Development of a comprehensive numerical model for analyzing a tubular-type indirect internal reforming SOFC - Nishino, T; Komori, H; Iwai, H; Suzuki, K (2003)
A numerical model for analyzing a tubular-type Indirect Internal Reforming Solid Oxide Fuel Cell (IIR-SOFC), which is expected to become one of the most important power generators in the near future, was developed. The model simultaneously treats momentum, heat and mass transfer, fuel reforming, electrochemical phenomena and an electric circuit. Calculations for the gas flow fields inside and outside the cell tube are conducted with a two-dimensional cylindrical coordinate system adopting the axisymmetric assumption. At the same time, the electric current field in the cell tube is calculated with a quasi three-dimensional coordinate system in order to consider the ohmic loss properly. Activation overpotential is also considered using a temperature dependent model. As a consequence of the calculations, details of conditions in the cell and its power generation characteristics were revealed. Serious temperature gradients were generated in the cell under circumstances where the catalyst for reforming was distributed uniformly inside the feed tube. Complicated electric current fields that varied in both the axial and circumferential direction of the cell were observed. In addition, it became obvious that the temperature dependency of the activation overpotential could be the most significant factor governing the power generation characteristics.